Relasi-relasi Kuasa dalam Praktik Agama Hindu yang ‘Ditemuciptakan’ di Bali - I Nyoman Wijaya (Universitas Udayana, 2015)
The purpose of this study is to discuss the relations of power in the history of the contemporary Hindu religion in Bali. The concept of power relations refers to the concept of Power and Discourse of Michel Foucault, while the term “invented religion” is a development of Invented Tradition by Eric Hobsbawm. “Invented religion” in this study is defined as the practice of Hindu religion, which was invented, constructed, and officially manifested; and the religious practice which emerged in a relatively short time; and in a few years it has been regarded as an established religion. Based on the concept of Power and Discourse of Foucault, I argue that there are relations of power that shape and sustain the practice of “invented religion.” I will try to find the power relations in a God worshipping discourse in Samuantiga and Jagatnatha temples. There are two research questions that I raise for the argument, namely how and why these two discourses emerge and thrive in contemporary’s practice of Hinduism? The answer to both questions will be sought at the present Balinese-Hindu intellectual thought. Then, it is assessed using the Genealogy Method of Foucault. My conclusion is that the presence of the two discourses is only to harmonize Hinduism with Islam as the majority religion in Indonesia.